Understanding Centenarians' Psychosocial Dynamics and Their Contributions to Health and Quality of Life. (21st July 2010) - Poon, Leonard W.; Martin, Peter; Bishop, Alex; Cho, Jinmyoung; da Rosa, Grace; Deshpande, Neha; Hensley, Robert; MacDonald, Maurice; Margrett, Jennifer; Randall, G. Kevin; Woodard, John L.; Miller, L. Stephen
Abstract : While it is understood that longevity and health are influenced by complex interactions among biological, psychological, and sociological factors, there is a general lack of understanding on how psychosocial factors impact longevity, health, and quality of life among the oldest old. One of the reasons for this paradox is that the amount of funded research on aging in the US is significantly larger in the biomedical compared to psychosocial domains. The goals of this paper are to highlight recent data to demonstrate the impact of four pertinent psychosocial domains on health and quality of life of the oldest old and supplement recommendations of the 2001 NIA Panel on Longevity for future research. The four domains highlighted in this paper are (1) demographics, life events, and personal history, (2) personality, (3) cognition, and (4) socioeconomic resources and support systems.